2018
DOI: 10.1007/s00125-018-4547-9
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in the older patient: heterogeneity requires individualisation of therapeutic strategies

Abstract: Owing to the worldwide increase in life expectancy, the high incidence of diabetes in older individuals and the improved survival of people with diabetes, about one-third of all individuals with diabetes are now older than 65 years. Evidence is accumulating that type 2 diabetes is associated with cognitive impairment, dementia and frailty. Older people with diabetes have significantly more comorbidities, such as myocardial infarction, stroke, peripheral arterial disease and renal impairment, compared with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 95 publications
5
53
1
3
Order By: Relevance
“…We found that diabetes duration, but not age, was directly related to the duration of hypoglycemia in patients treated with sulfonylureas. The duration of diabetes and age have previously been shown to be associated with the incidence of hypoglycemia in patients with type 2 diabetes in other treatment settings [21][22][23] . Furthermore, we found that the dose of sulfonylureas was associated with the duration of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…We found that diabetes duration, but not age, was directly related to the duration of hypoglycemia in patients treated with sulfonylureas. The duration of diabetes and age have previously been shown to be associated with the incidence of hypoglycemia in patients with type 2 diabetes in other treatment settings [21][22][23] . Furthermore, we found that the dose of sulfonylureas was associated with the duration of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive discussion of this area has been published by an expert review group and the results of subgroup analyses relating to event rate by age of various cardiovascular outcome trials has also been recently examined . We summarize the results of the outcome studies for both older and newer blood glucose‐lowering agents in and in which we also report recently released data from the CARMELINA trial.…”
Section: Cardiovascular Benefits and The Safety Of Older And Newer Glmentioning
confidence: 99%
“…These outcome trials have involved three dipeptidyl peptidase-4 (DPP-4) inhibitor trials, four glucagon-like peptide 1 (GLP-1) receptor agonist trials and two sodium-glucose cotransporter 2 (SGLT2) inhibitor trials [36]. A comprehensive discussion of this area has been published by an expert review group [36] and the results of subgroup analyses relating to event rate by age of various cardiovascular outcome trials has also been recently examined [37]. We summarize the results of the outcome studies for both older and newer blood glucose-lowering agents in Tables S3and S4 in which we also report recently released data from the CARMELINA trial.…”
Section: Cardiovascular Benefits and The Safety Of Older And Newer Glmentioning
confidence: 99%
“…One disease also associated with low muscle strength is diabetes . In older patients with diabetes, cross‐talk between insulin resistance, inflammation of adipose tissue, and inflammation of skeletal muscle can contribute to sarcopenia and frailty …”
Section: Introductionmentioning
confidence: 99%
“…4 In older patients with diabetes, cross-talk between insulin resistance, inflammation of adipose tissue, and inflammation of skeletal muscle can contribute to sarcopenia and frailty. 5 Alanine aminotransferase (ALT) is an emerging biomarker of frailty in older adults. 6 In several cohort studies, low-to-normal ALT has been shown to increase frailty, all-cause mortality and cardiovascular mortality.…”
Section: Introductionmentioning
confidence: 99%